Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.2196/12010
|View full text |Cite
|
Sign up to set email alerts
|

Exoskeletons With Virtual Reality, Augmented Reality, and Gamification for Stroke Patients’ Rehabilitation: Systematic Review

Abstract: BackgroundRobot-assisted therapy has become a promising technology in the field of rehabilitation for poststroke patients with motor disorders. Motivation during the rehabilitation process is a top priority for most stroke survivors. With current advancements in technology there has been the introduction of virtual reality (VR), augmented reality (AR), customizable games, or a combination thereof, that aid robotic therapy in retaining, or increasing the interests of, patients so they keep performing their exer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 61 publications
0
44
0
Order By: Relevance
“…Very few studies ( 25 , 26 ) have attempted to assess the additional benefits of this combination of technologies. Patients #1 and #5 in our study showed marginal motor improvements on the FM UE scale ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies ( 25 , 26 ) have attempted to assess the additional benefits of this combination of technologies. Patients #1 and #5 in our study showed marginal motor improvements on the FM UE scale ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…• Helpful for the therapy of the patient suffering the mental health issues Riva et al, 2011 44 ; Valmaggia et al, 2016 45 ; Chirico et al, 2016 46 ; Mubin et al, 2019 47…”
Section: Future Scopementioning
confidence: 99%
“…Robotic rehabilitation can reduce the burden of therapists by automating tedious and labor-intensive therapy [ 2 ] and by adapting to the specific needs of the targeted individuals [ 1 ]. Additionally, it can offer a multisensory rehabilitation experience [ 11 ] when combined with other technologies such as virtual and augmented reality (VR/AR) and gaming [ 12 ] or haptics [ 13 ]. This way it can provide additional sensory feedback to facilitate neuroplasticity and become more intuitive for individuals with cognitive deficiencies [ 13 ].…”
Section: Introductionmentioning
confidence: 99%